Immigration and the emergence of right-wing violence in unified Germany - Maier-Katkin, Daniel (Crime, law and social change, 1995)
The articles that make up this special issue were all derived from presentations at a conference that took place at the Pennsylvania State University in the Fall of 1993. This paper presents an overview of the themes and issues discussed at that conference. While the conference was broadly international, co-sponsored by Penn State University and the Max-Planck-Institut and supported financially by the DAAD, the articles included in this special issue focus principally on the nature and amount of hate crimes and xenophobia in Germany. This article describes the international and comparative nature of the conference and explains the decision to focus on the German situation.